2016
DOI: 10.7717/peerj.2079
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the structural and evolutionary characteristics for toll-like receptor 15

Abstract: Toll-like receptors (TLRs) play important role in the innate immune system. TLR15 is reported to have a unique role in defense against pathogens, but its structural and evolution characterizations are still poorly understood. In this study, we identified 57 completed TLR15 genes from avian and reptilian genomes. TLR15 clustered into an individual clade and was closely related to family 1 on the phylogenetic tree. Unlike the TLRs in family 1 with the broken asparagine ladders in the middle, TLR15 ectodomain had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…2014 ; Vinkler et al. 2014 ; Wang, Zhang, Chang, et al. 2016 ) and studies that described the functionally relevant residues for TLR1 ( Jin et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2014 ; Vinkler et al. 2014 ; Wang, Zhang, Chang, et al. 2016 ) and studies that described the functionally relevant residues for TLR1 ( Jin et al.…”
Section: Methodsmentioning
confidence: 99%
“…2008 ; Guan et al. 2010 ; Jang and Park 2014 ), TLR15 ( Wang, Zhang, Chang, et al. 2016 ), and TLR21 ( Keestra et al.…”
Section: Methodsmentioning
confidence: 99%
“…In the present work we provide evidence that (i) TLR15 is evolutionarily older than expected, (ii) tlr15 genes display species-specific codon usage, (iii) the tlr15 gene underwent evolutionary regression in most vertebrates including certain reptilian lineages, and (iv) that the activation of reptilian TLR15 by external proteases is a conserved feature that functionally distinguishes TLR15 from other TLR1 subfamily members. TLR15 was originally identified in chickens ( 17 ) and later studies found additional TLR15 orthologs in other avian and also four reptilian species (green anole lizard, Burmese python, Chinese alligator, and American alligator) ( 6 , 16 , 29 ). By combining phylogenetic and synteny analyses results, we identified TLR15 orthologs in even more reptilian species.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB reporter assays with TLR15-transfected cells clearly showed that the cloned reptilian TLR15 was proteolytically cleaved and activated by fungal proteases, as has previously been reported for chicken TLR15 ( 15 , 16 ). Chicken and reptilian TLR15 are predicted to share many structural characteristics including a highly conserved region in LRR11 which may be involved in the TLR15 activation process ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It appears that TLR15 is unique to birds and some reptilian species. TLR15 responds to in Salmonella enterica infections and is reported to have a unique auto‐activation mechanism . The avian TLR21 is an ortholog of the TLR21 proteins from teleost and amphibian species, and clusters into the TLR11 subfamily.…”
Section: Introductionmentioning
confidence: 99%